if (x^2+2)= x^4+10x^2+4 what is f(x^2-2)

if (x^2+2)= x^4+10x^2+4 what is f(x^2-2)

Given f(x)=x2, after performing the following transformations: shift upward 86 units and shift 57 units to the right, the new function g(x)=

A. The graph of g(x)=⌈x⌉+7 is the graph of f(x)=⌈x⌉ shifted down 7 units. B. The graph of g(x)=⌈x⌉+7 is the graph of f(x)=⌈x⌉ shifted right 7 units. C. The graph of g(x)=⌈x⌉+7...

A. Multiplying by 2 compresses the graph of g(x)=2⌈x⌉ vertically by a factor of 2. B. Multiplying by 2 stretches the graph of g(x)=2⌈x⌉ vertically by a factor of 2. C. Multiplying...

"Suppose g is the inverse function of a differentiable function f, and G(x)=1/g(x). If f(3)=7 and f'(3)=1/9, find G'(9). FInd G'(7)." Please show all steps- thanks so much...

Please show work

The integral from 0 to 27 of f(x)dx is 0.46896. I need to know what the function for f(x) is. The two endpoints of the curve are (0,0) and (27,0.2894).

Let f(x)=3x-1 and g(x)=x^2+4 find (f g)(-2)

Find a formula for f(x), an exponential function such that f(−8) = 200 and f(30) = 580

f(x) = 8x2 -7x g(x) = 8x - 4 (fog)(x) I would really appreciate the steps and final outcome of this problem. Thank you!

a) (-0.67, 1.00) b) (-6.2) c) (-0.33, -0.67) d) (-1.50, 0.50)

a) (2.09, -0.84) b) (-4.5) c) (-1.25, -1.75) d) (-0.57, 0.71)

For the following sum √(6+(3/n))(3/n)+√(6+(6/n))(3/n)+…+√(6+(3n/n))(3/n) is a right Reimann sum for the definite integral ∫f(x)dx with upper bound b and...

f(x) = 3x2 - 2x -3 f(x-1) = I would really appreciate the steps and final outcome of this problem. Thank you!

I dont understand how to solve quadratic functions. I'm supposed to solve f(x)-x^2+2x-3 by completing the square but whenever I try to search how to do these kind of problems, I never see...

Given f(x)=(x+5)(x-4)(x+2), Find the roots in increasing order To the left of the first root, is the graph of f(x) above or below the x-axis? Answer above or below: . Between...

the expression 210x-1210-3x can be written as 2f(x), where f (x) is the function of x. find f (x) f(x)=